Narrativas de 4 estudiantes de psicología entre las edades de 25-28 años sobre la red social Instagram y su relación con la autoestima. (2023)
The present research had the objective of analyzing the narratives of psychology students between 25-28 years old about the social network Instagram and its relationship with selfesteem, a qualitative methodological framework of descriptive scope with a narrative design was used. We had the participation of 4 people, 2 women and 2 men between the ages of 25-28 years from the city of Bogota, who are active users of the Instagram platform.